Politicized Spaces and Public Intimacy: The Cookery Books of Henrietta Maria and Elizabeth Cromwell - Grant, Priya (Cuizine)

(untitled) (McGill University Library, 2013)
Throughout the periods of the Protectorate and Restoration, images and texts concerning Henrietta Maria and Elizabeth Cromwell were widely circulated for public consumption. Two such documents, themselves examples of royalist propaganda, took the form of recipe books entitled, Queens Closet Opened and The Court & Kitchin of Elizabeth, commonly called Joan Cromwel. These books were published within the same decade, within which the Protectorate failed and the Restoration began. Both highlight the failures of Elizabeth, as representative of the protectorate, and praise Henrietta Maria as an emblem of the monarchy, both past and present. This article examines these cookery books in relation to the political movements the two women inevitably came to represent.